Polymer particles, diaphragm slurry, diaphragm and secondary battery

By using imide ring structure and polymer particles with multi-wrinkle surfaces, the problem of insufficient thermal stability and compatibility of lithium-ion battery separators at high temperatures is solved, and the cycle stability and specific energy density of the battery are improved, ensuring that Battery safety.

CN119161579AInactive Publication Date: 2024-12-20SHENZHEN HAODYNE TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411578508.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separator materials have poor thermal stability at high temperatures, which can easily lead to internal short circuits and insufficient compatibility with the electrolyte, affecting electrochemical performance.

Method used

Develop a polymer particle with an imide ring structure and a multi-pleated surface for the preparation of separator paste and separator, which improves electrolyte wetting and ion conduction paths by forming physical adsorption with binders, and at high temperature conditions Maintain good physical performance.

Benefits of technology

It improves the cycle stability and specific energy density of the battery, reduces the risks during battery use, and ensures the safe operation of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161579A_ABST
    Figure CN119161579A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of battery materials, particularly to a polymer particle, a diaphragm slurry, a diaphragm and a secondary battery, the polymer particle comprises an imide ring structure unit, and the glass transition temperature of the polymer particle is greater than 250 DEG C; the polymer particle has a multi-fold surface, the polymer particle can still keep good physical performance and stable chemical performance at high temperature, the imide structure has good affinity with an electrolyte, the particle with the multi-fold surface is large in specific surface area, and the absorption and retention capacity of the electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to polymer particles, diaphragm slurry, diaphragm and secondary battery. Background Art

[0002] As a highly efficient energy storage device, lithium-ion batteries play a key role in portable electronic products, electric vehicles and large-scale energy storage systems. The separator is one of the key components of lithium-ion batteries. It not only needs to ensure the physical isolation between the positive and negative electrodes to prevent internal short circuits, but also needs to provide a fast and efficient transmission channel for lithium ions. Therefore, the performance of the separator material directly affects the safety and electrochemical performance of the battery.

[0003] Traditional polyolefin (such as polyethylene PE and polypropylene PP) separators are widely used due to their low cost and easy processing, but they have some disadvantages, such as low thermal stability, which may lead to melt shrinkage at high temperatures, thereby increasing the risk of internal short circuits. In addition, the wettability between polyolefin separators and electrolytes is poor, which affects the electrochemical performance of the battery.

[0004] To overcome these problems, researchers have developed a variety of modification schemes. Among them, a common method is to coat a layer of ceramic material (such as aluminum oxide Al2O3 or silicon dioxide SiO2) on the surface of the polyolefin separator to improve the thermal stability and mechanical strength of the separator. However, this ceramic coating layer has poor compatibility with the polyolefin base membrane and may gradually peel off during the battery charging and discharging process, causing the separator to fail. In addition, the higher density of the ceramic coating will increase the weight of the battery, which is not conducive to improving the specific energy of the battery.

[0005] As a high-performance polymer, polyimide (PI) has excellent thermal and chemical stability, making it an ideal choice to replace traditional coating materials. PI coating can significantly improve the heat resistance and mechanical properties of the diaphragm, and its unique imide structure helps to enhance the affinity with the electrolyte and improve the wettability of the diaphragm. However, directly coating the diaphragm with PI glue may cause pore blockage, reduce the permeability of the diaphragm, and affect the transmission efficiency of lithium ions.

[0006] Patent CN108346765A discloses a polyimide-coated polyolefin diaphragm; the polyimide coating improves the compatibility and adhesion between the polyolefin base diaphragm and the coating layer, and can effectively improve the ionic conductivity and the cycle performance of lithium-ion batteries. However, the use of polyimide glue coating may cause diaphragm pore blockage and reduce air permeability.

[0007] Therefore, it is of great significance to develop polymer particles with good thermal stability and mechanical strength for use in separator slurry, separator and secondary battery. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a polymer particle, a separator slurry, a separator and a secondary battery.

[0009] In a first aspect, a polymer particle comprises an imide ring structural unit, the polymer particle has a glass transition temperature greater than 250° C., and the specific surface area of ​​the polymer particle is 60-130 m 2 / g, the polymer particles have a multi-fold surface.

[0010] The polymer particles in the present invention are polymer particles with a multi-corrugated surface, and the imide ring structural unit thereof can form strong physical adsorption with the binder, thereby avoiding the phenomenon of powder shedding and falling off of the secondary battery prepared by using the imide ring structure during use. At the same time, the imide ring structure has good affinity with the electrolyte, and the multi-corrugated surface morphology increases the specific surface area of ​​the particles, which is beneficial to the electrolyte infiltration, optimizes the ion conduction path, and thus improves the battery's charge and discharge efficiency and cycle stability. In addition, the polyimide itself has thermal stability and mechanical strength, so that it can still maintain good physical properties under high temperature conditions, thereby ensuring the safe operation of the battery.

[0011] Preferably, the glass transition temperature of the polymer particles is 250°C-450°C Preferably, the molar ratio of the amino monomer to the carboxylic anhydride monomer is (0.95-1.05): 1. If the molar ratio of the amino monomer to the carboxylic anhydride monomer is greater than or less than (0.95-1.05): 1, the molecular weight of the polymer particles will be low, and it will be difficult to form particles with regular morphology.

[0012] In the present invention, the molar ratio of the amino monomer to the carboxylic anhydride monomer may be 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1 or 1.05:1, etc.

[0013] Preferably, the polymer particles have a D50 particle size of 0.2-3 μm.

[0014] In the present invention, the particle size D50 of the polymer particles may be 0.2, 0.5, 1.0, 1.5, 2.0, 2.5 or 3.0 μm, etc.

[0015] In the present invention, by controlling the D50 particle size of the polymer particles within a specific range, a diaphragm with excellent performance can be prepared. If the D50 particle size of the polymer particles is too small, the wettability of the diaphragm electrolyte will deteriorate. If the D50 particle size of the polymer particles is too large, the heat shrinkage resistance of the diaphragm will decrease under the same coating thickness. In addition, if the D50 particle size is too large, it is difficult to prepare a coating of the desired thickness.

[0016] Preferably, the amino monomer structural unit is selected from one or more of 1,2-phenylenediamine, 1,3-phenylenediamine, 1,4-phenylenediamine, 4,4'-diaminobiphenyl, 3,3'-diaminodiphenyl sulfone, and 3,5-diaminobenzoic acid.

[0017] Preferably, the carboxylic anhydride monomer structural unit is selected from one or more of pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride), butanetetracarboxylic dianhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride.

[0018] The present invention also provides a method for preparing polymer particles, comprising the following steps: (1) adding an amino monomer and a salt-forming agent into a container filled with deionized water, stirring until dissolved, adding a carboxylic anhydride monomer structural unit, and reacting at 0-80° C. to obtain a polyamic acid salt aqueous solution; (2) adding a surfactant to the polyamic acid salt aqueous solution, stirring evenly, pouring into a hydrothermal reactor, reacting at 150-200° C. for 2-12 hours, cooling to room temperature after the reaction is completed, filtering, separating, and precipitating the initial product, washing with deionized water, and drying to obtain partially imidized polymer particles with a multi-fold surface; (3) The polymer particles obtained in (2) are subjected to imidization reaction at 300-500° C. for 1-3 hours to obtain fully imidized polymer particles having a multi-wrinkled surface.

[0019] In the present invention, the salt-forming agent is an organic tertiary amine compound or an inorganic base, specifically selected from one or more of triethylamine, 1,2-dimethylimidazole, and lithium hydroxide, and the molar ratio of the salt-forming agent to the anhydride monomer is (2-4):1; the surfactant is selected from one or more of N,N-dimethyldodecylamine and N,N-dimethylhexadecylamine, and the molar ratio of the surfactant to the anhydride monomer is (0-3):1.

[0020] In a second aspect, the present invention provides a diaphragm slurry, the raw materials of which include, by weight: 100 parts of polymer particles and inorganic particles in total, 1-10 parts of a binder, 230-300 parts of deionized water, 0.5-3 parts of a wetting agent, 0.3-2 parts of a defoaming agent, and 0.5-3 parts of an anti-settling agent.

[0021] Preferably, the mass ratio of the polymer particles to the inorganic particles is (10-100):(0-90).

[0022] In the present invention, the mass ratio of the polymer particles to the inorganic particles may be 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, 90:10 or 100:0, etc.

[0023] The polymer particles in the present application can be used to partially replace or completely replace the inorganic particles in the prior art diaphragm slurry, and a slurry composition with excellent performance is prepared. The imide ring structure has good affinity with the electrolyte, and the wrinkled surface morphology increases the specific surface area of ​​the particles, which is beneficial to the electrolyte infiltration and optimizes the ion conduction path, thereby making the diaphragm prepared from the diaphragm slurry light and having good heat resistance and electrolyte wettability.

[0024] Preferably, the inorganic particles have a D50 particle size of 0.2-2 μm.

[0025] In the present invention, the particle size D50 of the inorganic particles may be 0.2, 0.5, 1, 1.5 or 2 μm, etc.

[0026] Among them, the inorganic particles are selected from one or a combination of two or more of silicon dioxide, aluminum oxide, boehmite, zirconium dioxide, magnesium hydroxide, zinc oxide, and titanium dioxide.

[0027] The binder is selected from one or a combination of two or more of polyvinyl alcohol, styrene-butadiene rubber, fluorinated rubber, styrene-butadiene polymer, polyvinylidene fluoride, polyacrylic acid, polymethacrylic acid, polyacrylate, polymethyl methacrylate, and polyacrylonitrile.

[0028] As a preferred technical solution of the present invention, the binder is selected from polyacrylate binders and / or styrene-butadiene latex binders.

[0029] It should be noted that the polyacrylate adhesive and the styrene-butadiene latex adhesive can be commercially available or homemade.

[0030] The anti-settling agent is selected from one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0031] In the present invention, the anti-settling agent can effectively prevent the polymer particles and inorganic particles in the slurry from settling, ensuring the uniformity and stability of the slurry during preparation and use. The thickening effect of the anti-settling agent can increase the viscosity of the slurry, prevent stratification and sedimentation, and improve the storage stability of the slurry. The anti-settling agent can improve the rheological properties of the slurry, making it easier to coat and process, thereby improving production efficiency.

[0032] The wetting agent is selected from one or more of acetylene glycol type wetting agents, fatty alcohol sulfate type wetting agents, and sulfonate type wetting agents.

[0033] In the present invention, the wetting agent can significantly reduce the surface tension of the slurry, improve the wettability and adhesion of the slurry to the substrate, ensure the uniform coating of the slurry, and will not have a negative impact on the battery performance.

[0034] The defoamer is selected from one or more of an organosilicon defoamer, a mineral oil defoamer, and a polyether defoamer.

[0035] It should be noted that there is no special limitation on the preparation method of the slurry composition in the present invention, and all commonly used preparation methods in the art are applicable, including but not limited to: uniformly mixing the components of the slurry composition to obtain the slurry composition.

[0036] In a third aspect, the present invention provides a composite membrane, comprising a substrate layer and a polymer coating disposed on one side or both sides of the substrate layer.

[0037] In the present invention, the base film is selected from one or more of a polyethylene porous film and a polypropylene porous film.

[0038] It should be noted that there is no special limitation on the thickness of the substrate layer and the thickness of the polymer coating in the present invention, and the thickness ranges commonly used in the art are applicable. The thickness of the substrate layer exemplarily includes but is not limited to: 7 μm, 12 μm, for example, 7 μm, 9 μm or 12 μm, etc.; the thickness of the polymer coating exemplarily includes but is not limited to 0.5 μm, 3 μm, for example, 0.5 μm, 1 μm, 2 μm or 3 μm, etc.

[0039] It should also be noted that if both sides of the diaphragm are provided with a polymer coating, the specific composition of the polymer coatings on both sides of the diaphragm may be the same or different, and the thickness of the polymer coatings on both sides of the diaphragm may be the same or different. It should also be noted that if both sides of the diaphragm are provided with a polymer coating, the specific composition of the polymer coatings on both sides of the diaphragm may be the same or different, and the thickness of the polymer coatings on both sides of the diaphragm may be the same or different.

[0040] Preferably, the membrane coating surface density is ≤0.55 mg / cm 2.

[0041] The polymer particles in the present application can be used to partially replace or completely replace the inorganic particles in the prior art. The diaphragm prepared using the polymer particles in the present application has the advantages of being light in weight and having good heat resistance and electrolyte wettability.

[0042] In the present invention, the coating amount of the diaphragm slurry in the diaphragm is 1-6 g / m 2 .

[0043] Preferably, the longitudinal heat shrinkage rate of the diaphragm is ≤2%.

[0044] Preferably, the transverse heat shrinkage rate of the diaphragm is ≤2%.

[0045] In a fourth aspect, the present invention provides a secondary battery comprising the separator described in the third aspect.

[0046] In the present invention, the secondary battery is selected from a lithium ion battery or a sodium ion battery, and the secondary battery further comprises a positive electrode, a negative electrode and an electrolyte.

[0047] In the present invention, if the secondary battery is selected from a lithium ion battery, the active material of the positive electrode is selected from one or more of lithium iron phosphate, ternary materials, lithium manganese oxide, and lithium cobalt oxide; the electrolyte in the electrolyte is selected from one or more of lithium hexafluorophosphate, ethylene carbonate, propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate.

[0048] In the present invention, if the secondary battery is selected from a sodium ion battery, the active material of the positive electrode is selected from one or more of sodium cobaltate, sodium manganate, and sodium ferrophosphide; the electrolyte in the electrolyte is selected from one or more of sodium hexafluorophosphate, ethylene carbonate, propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate.

[0049] Compared with the prior art, the present invention has the following beneficial effects: (1) The polymer particles with multi-fold surfaces of the present invention have imide ring structural units that can form strong physical adsorption with the binder, thereby preventing the secondary battery prepared using the imide ring structure from falling off during use. At the same time, the imide ring structure has good affinity with the electrolyte, and the multi-fold morphology of the surface increases the specific surface area of ​​the particles, which is beneficial to the electrolyte infiltration, optimizes the ion conduction path, and thus improves the cycle stability of the battery. In addition, the polyimide itself has thermal stability and mechanical strength, so that it can still maintain good physical properties under high temperature conditions, thereby ensuring the safe operation of the battery.

[0050] (2) The present invention uses polymer particles in the diaphragm slurry to prepare the diaphragm. The multi-fold surface morphology increases the specific surface area of ​​the particles, which is beneficial to the electrolyte infiltration, optimizes the ion conduction path, and further improves the cycle stability of the battery. The polymer particles themselves have thermal stability and mechanical strength, which prevents deformation or melting at high temperatures, thereby ensuring the safe operation of the battery.

[0051] (3) The present invention uses a separator for a secondary battery, so that the secondary battery has a higher specific energy density and a longer cycle life, meeting the requirements of a high-performance battery. In addition, the high thermal stability and mechanical strength of the separator improve the safety of the battery and reduce the risk of the battery during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a scanning electron microscope image of the polymer particles prepared in Example 3. DETAILED DESCRIPTION

[0053] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0054] Example 1

[0055] This embodiment provides a method for preparing polymer particles, comprising the following steps: (1) Add 1,3-phenylenediamine and 1,2-dimethylimidazole into a container filled with deionized water, stir until dissolved, add 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride, and react at 60° C. for 12 hours to obtain a polyamic acid salt aqueous solution; (2) adding dodecyldimethylamine to the polyamic acid salt aqueous solution, stirring evenly, pouring into a hydrothermal reactor, reacting at 180° C. for 12 h, cooling to room temperature after the reaction is completed, filtering, separating, and precipitating the initial product, washing with deionized water, and drying to obtain a solid product; (3) The solid product was subjected to an imidization reaction under nitrogen at 300°C for 2 hours to obtain imidized polymer particles with a D50 particle size of 1.4 μm.

[0056] Among them, the molar ratio of 1,3-phenylenediamine to 3,3',4,4'-benzophenone tetracarboxylic dianhydride is 0.95:1, the molar ratio of 1,2-dimethylimidazole to 3,3',4,4'-benzophenone tetracarboxylic dianhydride is 2.2:1, and the molar ratio of dodecyldimethylamine to 3,3',4,4'-benzophenone tetracarboxylic dianhydride is 2.8:1.

[0057] Example 2 Compared with Example 1, the molar ratio of 1,3-phenylenediamine to 3,3',4,4'-benzophenonetetracarboxylic dianhydride is 0.97:1.

[0058] Example 3

[0059] Compared with Example 1, the molar ratio of 1,3-phenylenediamine to 3,3',4,4'-benzophenonetetracarboxylic dianhydride is 1:1.

[0060] Example 4

[0061] Compared with Example 1, the molar ratio of 1,3-phenylenediamine to 3,3',4,4'-benzophenonetetracarboxylic dianhydride is 1.02:1.

[0062] Example 5

[0063] Compared with Example 1, the molar ratio of 1,3-phenylenediamine to 3,3',4,4'-benzophenonetetracarboxylic dianhydride is 1.05:1.

[0064] Example 6

[0065] Compared with Example 1, the amino monomer is 4,4'-diaminobiphenyl, the anhydride monomer is 3,3',4,4'-biphenyltetracarboxylic acid dianhydride in a molar ratio of 1:1, the molar ratio of 2-dimethylimidazole to 3,3',4,4'-biphenyltetracarboxylic acid dianhydride is 2.6:1, and the molar ratio of dodecyl dimethylamine to 3,3',4,4'-biphenyltetracarboxylic acid dianhydride is 2.6:1.

[0066] Example 7

[0067] Compared with Example 1, the amino monomer is 1,4-phenylenediamine, the anhydride monomer is pyromellitic anhydride in a molar ratio of 1:1, the molar ratio of 2-dimethylimidazole to pyromellitic anhydride is 3.0:1, and the molar ratio of dodecyldimethylamine to 3,3',4,4'-biphenyltetracarboxylic anhydride is 3.0:1.

[0068] Comparative Example 1 Compared with Example 1, the molar ratio of 1,3-phenylenediamine to 3,3',4,4'-benzophenone tetracarboxylic dianhydride is 0.9:1, and the remaining steps are the same as in Example 1.

[0069] Comparative Example 2 Compared with Example 1, the molar ratio of 1,3-phenylenediamine to 3,3',4,4'-benzophenone tetracarboxylic dianhydride is 1.1:1, and the remaining steps are the same as in Example 1.

[0070] Comparative Example 3 Compared with Example 1, the mass ratio of polymer particles to BG611 is 5:95, and the remaining steps are the same as Example 1.

[0071] Comparative Example 4 Compared with Example 1, the polymer particles are commercially available polystyrene microspheres with a D50 particle size of 1.5 μm, and the remaining steps are the same as Example 1.

[0072] Comparative Example 5 Compared with Example 1, the ratio of polymer particles to inorganic particles is 0:100, and the remaining steps are the same as Example 1.

[0073] The polymers of Examples 1 to 7 and Comparative Examples 1 to 3 were characterized and tested for performance. The test results are shown in Table 1.

[0074] Particle size: The particle size of the polymer particles was measured using a laser particle size analyzer (Zhuhai OMEC Instrument Co., Ltd., model: LS-909E).

[0075] Glass transition temperature: The glass transition temperature Tg of the separator binder B was measured using a differential scanning calorimeter (Shanghai Qunhong Instrument Equipment Co., Ltd., model: DSC-100).

[0076] Specific surface area of ​​polyimide polymer particles: Referring to GB / T19587-2017, the nitrogen adsorption specific surface area analysis test method was used for testing and the result was calculated using the BET (BrunauerEmmettTeller) method. The nitrogen adsorption specific surface area analysis test was performed using a specific surface area pore size analyzer (Micromeritics, model: Tri-Star3020).

[0077] The performance of Examples 1 to 7 and Comparative Examples 1 to 5 were tested, and the test results are shown in Tables 1 to 3.

[0078] Table 1

[0079] It can be seen from the results in Table 1 that when the molar ratio of the amino monomer to the carboxylic anhydride monomer is greater than or less than (0.95-1.05):1, the molecular weight of the polymer particles will be low and it will be difficult to form particles with regular morphology.

[0080] Diaphragm 1 The polymer particles in Example 3 are prepared into a diaphragm, and the preparation method of the diaphragm is as follows: Add 250 parts of deionized water and 2 parts of carboxymethyl cellulose into a high-speed mixer, and disperse them at 500 r / min for 30 minutes. Then add polymer particles, inorganic particles BG611, and 8 parts of polyvinyl alcohol, and disperse them at 1200 r / min for 2 hours. Then add 1 part of SURFYNOL 104E and 1 part of BYK-024, and disperse them at 300 r / min for 30 minutes to obtain a diaphragm slurry.

[0081] Among them, the mass ratio of polymer particles to BG611 is 10:90.

[0082] The present invention also provides a method for preparing a diaphragm, wherein the prepared diaphragm slurry is coated on a 7 μm polyethylene porous membrane, and the coating dry film thickness is controlled to be 2 μm, and the membrane is rolled up to obtain the diaphragm.

[0083] Diaphragm 2 Compared with the separator 1, the mass ratio of polymer particles to BG611 is 30:70.

[0084] Diaphragm 3 Compared with membrane 1, the mass ratio of polymer particles to BG611 is 50:50.

[0085] Diaphragm 4 Compared with the separator 1, the mass ratio of polymer particles to BG611 is 70:30.

[0086] Diaphragm 5 Compared with membrane 1, the mass ratio of polymer particles to BG611 was 100:0.

[0087] Diaphragm 6 Compared with the separator 1, the polymer particles are the polymer particles in Example 6, and the mass ratio of the polymer particles to BG611 is 100:0.

[0088] Diaphragm 7 Compared with the separator 1, the polymer particles are the polymer particles in Example 7, and the mass ratio of the polymer particles to BG611 is 50:50.

[0089] Comparison Diaphragm 1 The polymer particles in Comparative Example 1 were used, and the remaining steps were the same as those in Diaphragm 1.

[0090] Comparative Example 2 The polymer particles in Comparative Example 2 were used, and the remaining steps were the same as those in Diaphragm 1.

[0091] Comparison diaphragm 3 Compared with membrane 1, the mass ratio of polymer particles to BG611 is 5:95.

[0092] Comparison Diaphragm 4 Compared with membrane 1, the polymer particles are commercially available polystyrene microspheres with a D50 particle size of 1.5 μm, and the remaining steps are the same as membrane 1.

[0093] Comparison Diaphragm 5 Compared with diaphragm 1, the ratio of polymer particles to inorganic particles is 0:100, and the remaining steps are the same as diaphragm 1.

[0094] The above membranes were subjected to air permeability tests, and the test results are shown in Table 2.

[0095] The test method for the air permeability time is: using a Gurley air permeability instrument for testing.

[0096] The single-side coating surface density test was performed on the above diaphragms, and the test results are shown in Table 2.

[0097] Single-sided coating surface density: Cut the polyethylene porous membrane and the diaphragm into several discs of the same size and known area, and calculate the average weight of the polyethylene porous membrane and the diaphragm individually. The single-sided coating surface density = (W1-W0) / (2S), where W1 is the average weight of the diaphragm discs, W0 is the average weight of the polyethylene porous membrane discs, and S is the disc area; in the present application, the single-sided coating surface density is the surface density when the coating thickness is 2μm.

[0098] The above diaphragms were subjected to a heat shrinkage resistance test, and the test results are shown in Table 2.

[0099] The test method for heat shrinkage resistance is: cut the diaphragm prepared by the scheme of the present invention into a specification of 100×100 mm, place it between two A4 papers, place it on an iron plate, transfer it to a 130°C oven and bake it for 1 hour, and test the change rate of the longitudinal width (MD) and the transverse width (TD) before and after.

[0100] The above diaphragms were subjected to electrolyte wettability tests, and the test results are shown in Table 2.

[0101] The electrolyte wettability test method is as follows: the diaphragm prepared by the scheme of the present invention is cut into strips with a width of 5 mm, 10 μL of electrolyte is dripped onto the diaphragm strips, and the length of electrolyte diffusion is observed after 1 minute.

[0102] Table 2

[0103] It can be seen from the results in Table 2 that when the polymer particles provided by the present invention are used and the diaphragm slurry composition obtained by configuring the polymer particles is applied to the diaphragm, at the same thickness, the coating surface density is significantly lower than the ceramic diaphragm of Comparative Example 5, the diaphragm air permeability time is significantly lower than the ceramic diaphragm of Comparative Example 5, and the longitudinal (MD) thermal shrinkage rate and transverse (TD) thermal shrinkage rate (≤2%) can be maintained. The electrolyte wettability is better than the ceramic diaphragm of Comparative Example 5.

[0104] Separators 1 to 7 and comparative separators 1 to 5 were prepared into lithium-ion batteries and tested. The preparation and testing methods are as follows: The battery preparation method is as follows: the negative electrode sheet, the positive electrode sheet, the electrolyte and the separator are assembled into a battery.

[0105] Preparation of positive electrode sheet: prepare HSV900 binder solution with a mass fraction of 7%, then add 28 parts by weight of N-methylpyrrolidone, 1 part of conductive carbon Super.P and 0.5 parts of conductive graphite KS6 into a double planetary mixer and stir for 1 hour, add 45 parts of binder solution, stir for 1.5 hours, and add 100 parts of DY-3 active material, stir for 30 minutes to obtain positive electrode slurry, and then scrape the positive electrode slurry on the carbon-coated aluminum foil and bake at 100°C for 1 minute to obtain the positive electrode sheet.

[0106] Preparation of negative electrode sheet: negative electrode materials graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene butadiene latex are mixed in a mass ratio of 94.5:1:2.25:2.25, deionized water is added to obtain negative electrode slurry, and then the negative electrode slurry is scraped and coated on the surface of copper foil, and the negative electrode sheet is obtained after drying.

[0107] Preparation of the electrolyte: In a glove box filled with argon, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate were mixed in a mass ratio of 3:2:5, lithium hexafluorophosphate was added, and the mixture was stirred evenly to obtain the electrolyte for the lithium ion battery.

[0108] Battery cycle performance test: The battery is charged to 4.5V at a constant current of 3000mA (1C) at 25°C, then charged at a constant voltage with a cut-off current value of 150mA, and then discharged to 3V at a constant current of 3000mA. This is considered one cycle. After repeating this process 500 times, the capacity retention rate after 500 cycles (%) is calculated as (discharge capacity after 500 cycles / initial discharge capacity) × 100%.

[0109] Table 3

[0110] The test results in Table 3 show that the polymer particles partially replace the inorganic particles, and the prepared separator has little effect on the battery capacity.

[0111] Combined with the data in Tables 1 to 3, in Application Examples 1 to Application Examples 7, the diaphragm slurry composition obtained by the provided polymer configuration has good thermal stability and electrolyte affinity, so that the prepared diaphragm has good heat shrinkage resistance and electrolyte wettability. Therefore, the lithium-ion batteries assembled in Application Examples 1 to Application Examples 7 have good cycle stability.

[0112] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A polymer particle, characterized in that The polymer particles include an imide ring structural unit, the glass transition temperature of the polymer particles is greater than 250° C., and the specific surface area of ​​the polymer particles is 60-130 m 2 / g, the polymer particles have a multi-fold surface.

2. The polymer particles according to claim 1, characterized in that The glass transition temperature of the polymer particles is 250-450°C.

3. The polymer particles according to claim 1, characterized in that The particle size of the polymer particles is 0.2-3 μm.

4. The polymer particles according to any one of claims 1 to 3, characterized in that The polymer particles are obtained by polymerizing a raw material composition including an amino monomer and a carboxylic anhydride monomer, and the molar ratio of the amino monomer to the carboxylic anhydride monomer is (0.95-1.05):

1.

5. A diaphragm slurry, characterized in that: The diaphragm slurry comprises the polymer particles according to any one of claims 1 to 4 and inorganic particles, and the mass ratio of the polymer particles to the inorganic particles is (10-100): (0-90).

6. A diaphragm, characterized in that: The diaphragm includes the diaphragm slurry according to claim 5.

7. The diaphragm according to claim 6, characterized in that The single-side coating surface density of the diaphragm is ≤0.55 mg / cm 2 .

8. The diaphragm according to claim 6 or 7, characterized in that: The longitudinal heat shrinkage rate of the diaphragm is ≤2%.

9. The diaphragm according to claim 6 or 7, characterized in that: The transverse heat shrinkage rate of the diaphragm is ≤2%.

10. A secondary battery, characterized in that: The secondary battery includes the separator according to claim 9.

Citation Information

Patent Citations

  • Novel polyimide microsphere slurry and coated diaphragm thereof

    CN114883746A

  • Method for preparing hierarchical structure polyimide material through hydrothermal polymerization

    CN116178715A

  • Polyimide porous microsphere coated diaphragm for lithium battery and preparation method of polyimide porous microsphere coated diaphragm

    CN116315447A

  • Lithium battery slurry coated diaphragm and preparation method and coating slurry thereof

    CN116487820A